Implementasi Pendekatan Science, Technology, Engineering, Mathematics (STEM) dalam Pembelajaran dan Hubungannya dengan Kemampuan Berpikir Kreatif Siswa - Novica Ashari; Zulyusri Zulyusri; Relsas Yogica; Heffi Alberida (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
STEM is a learning approach that integrates 4 disciplines in learning, namely science, technology, engineering and mathematics. This approach aims to form the next generation that meets the abilities of the 21st century, one of which is the ability to think creatively. It is important for students to develop creative thinking skills to make students think rationally in solving a problem. The average level of creative thinking of students has various percentages. The purpose of this study was to examine the results of implementing the STEM approach in biology learning from 10 relevant articles and their relationship to students' creative thinking abilities. The type of research used is a meta-analysis with a literature review research method using several data sources such as articles in electronic journals and books. The results showed that the application of the STEM approach in learning had an effect on increasing students' creative thinking skills.